The sleeping beauty it’s a research and analysis of some traditional versions and rewritings - Ramírez S., Natalia (2014)
It’ s an essay that tries to crystallise the límits and the stereotypes that we have read about women in fairy tales in Children literature. We have analysed the most famous and well known fairy tale that everybody loves The Sleeping Beauty. We are going to revise the traditional versions and analyse the same content by three approaches: The Feminist, The Jungian and The Psychoanalytic. Finally, nowadays we have shown rewriting versions and after the analysis we have just arrived to the conclusions.